The presence of bifidobacteria in social insects, fish and reptiles - Kopecný, J; Mrázek, J; Killer, J (Folia microbiologica, 2010)
The occurrence and species distribution of bifidobacteria in the digestive tract of important representatives of social insects such as ants, bees, wasps and bumblebees as well as the incidence of bifidobacteria in fecal samples of several species of vertebrates represented mainly by reptiles was assigned by culture-independent method based on DGGE and real time PCR. Bifidobacteria were present in the gut of most social insects--honey bees, wasps, cockroaches and bumblebees, except for ants. In honey bees, where the counts of bifidobacteria ranged from 2 to 8% of the total bacteria, the most common species seemed to be Bifidobacterium indicum. Proportion of bifidobacteria was found in broad range from 0.1 to 35-37% in wasps and cockroaches; the variance of bifidobacteria in bumblebees was lower, ranging from 1 to 7% of total bacterial count. Among studied vertebrates, the detectable presence of bifidobacteria was found only in trout (1.1%) and geckos (0.2%), but large amount of these bacteria was observed in Vietnamese box turtle, where bifidobacteria represented nearly one-fourth (22%) of total bacterial counts.
Keywords: Electrophoresis, Polyacrylamide Gel; denaturace nukleových kyselin; DNA bakterií; feces; hmyz; elektroforéza v polyakrylamidovém gelu; DNA, Ribosomal; ryby; Sequence Analysis, DNA; RNA ribozomální 16S; zvířata; RNA, Ribosomal, 16S; Reptiles; Insecta; Feces; sekvenční analýza DNA; DNA, Bacterial; Fishes; Nucleic Acid Denaturation; polymerázová řetězová reakce; Polymerase Chain Reaction; plazi; ribozomální DNA; Animals; Bifidobacterium